Perkembangan Fisik Motorik Anak Berdasarkan Tingkat Sosial Ekonomi Keluarga di Kabupaten Bima - Andriani Andriani; Neneng Agustiningsih (UIN Mataram, 2023)
This study aims to determine of the physical and motor development of children aged 3-4 years in Bima Regency, West Nusa Tenggara. The approach of research is quantitative, and the type of research is correlation research. The population in this study were 79 families with the target of children aged 3-4 years and their parents, with number of samples to be studied is 38 families with a sample technique using disproportionate stratified random sampling. The method of collecting data is through questionnaires and observation to obtain information relevant to the research. The analysis data is descriptive, so the results of analysis show that the socio-economic level of the family is in the middle category and the physical motor development of children aged 3-4 years is in the category of developing according to expectations, and the correlation coefficient between variable X and variable Y is 0.033 and the value of r the table for N=38 is 0.325 meaning Ha is accepted and Ho is rejected, that mean the physical motor development of children aged 3-4 years effected by the socio-economic level of the family.